Combining anthropometry and bioelectrical impedance analysis to predict body fat in female athletes - Foote, D. M.; Berkelhammer, M.; Marone, J.; Horswill, C. A. (Journal of Athletic Training, 2022)
Context: Accurate methods for predicting the percentage of body fat (%Fat) in female athletes are needed for those who lose weight before competition. Methods mandated by sport governing bodies for minimal weight determination in such athletes lack validation.